ANALISIS HUKUM ATAS PERAN DAN TANGGUNG JAWAB DIREKTUR NOMINEE DALAM PERSEROAN TERBATAS - Muhammad Anwar Ibrahim (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study aims to analyze the role and legal responsibilities of nominee directors in Indonesian limited liability companies and to evaluate the legal challenges they face. The research findings indicate that while nominee directors represent the interests of third parties or majority shareholders, they remain bound by fiduciary duties and applicable laws, such as good faith, loyalty, and diligence. However, existing laws have not fully addressed potential conflicts of interest between the nominating parties' instructions and the company's interests. The conclusion emphasizes the need for enhanced regulations and stricter implementation of international practices to strengthen corporate governance in Indonesia, enabling nominee directors to operate effectively and support the growth and sustainability of limited liability companies